Chronic obstructive pulmonary disease: a modifiable risk factor for cardiovascular disease?. Issue 14 (27th June 2012) - Stone, Ian S; Barnes, Neil C; Petersen, Steffen E
Abstract : Significant cardiac morbidity and mortality exists in patients with COPD. Shared risk factors include age, smoking history and exposure to air pollution and passive smoke. Although the inappropriate under-prescribing of β-blockers contributes, it is now appreciated that the observed cardiac risk is not only due to smoking and conventional cardiovascular risk factors, but also other independent factors. A number of hypotheses exist for the increased cardiovascular morbidity and mortality seen in COPD including inflammation, pulmonary hypertension, lung hyperinflation and shared genetics models. Mounting evidence from large randomised controlled trials suggests that COPD treatment may be cardio-protective. We review the current evidence supporting the aforementioned hypotheses and how their modulation may prevent cardiovascular morbidity and mortality in COPD. The persisting underdiagnosis of COPD may have significant consequences. Further mechanistic studies identifying the onset and impact of individual interventions will develop our understanding of this emerging and highly relevant clinical field.